Development of Digital Teaching Materials about Surakarta Culinary in History Learning - Djono; Sutiyah; Sudiyanto; Sukmawati, Fatma; Salimi, Moh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The development of educational technology in the 21st century must be in line with the preservation of the nation’s culture. For this reason, digital teaching materials are needed that contain culinary culture to preserve the nation’s culture and nationalism for the next generation. Therefore, this study aims to develop digital teaching materials about Surakarta culinary. This research was conducted as research and development by following the ADDIE research and development procedure (Analysis, Design, Development, Implementation, and Evaluation). This research was carried out until the development stage with the research subjects consisting of 278 high school students in Surakarta City. The research subjects were determined using a purposive technique with the consideration of the History teacher at the school. The data collection technique used a questionnaire distributed through google form. The questionnaire used in this study is a closed questionnaire with 21 statements to analyze the needs of the required teaching materials. Data analysis was then carried out using quantitative and qualitative techniques with a descriptive approach. The results of the study revealed that (1) most students expressed interest in using digital teaching materials, (2) Students hoped that teaching materials in the form of electronic books could facilitate the learning process from anywhere. (3) although students are familiar with various types of traditional culinary in the city of Surakarta, only a few understand the philosophy of the typical food of the city of Surakarta, and (4) the product of digital teaching materials for the history of the culinary city of Surakarta that was developed is suitable for use in the classroom learning process. The results of this research and development can be the basis for further research and development to develop innovative teaching materials that are suitable for use to improve the success of the learning process.